2015
DOI: 10.3390/molecules201017913
|View full text |Cite
|
Sign up to set email alerts
|

Potent Activities of Roemerine against Candida albicans and the Underlying Mechanisms

Abstract: Roemerine (RM) is an aporphine alkaloid isolated from the fresh rattan stem of Fibraurea recisa, and it has been demonstrated to have certain antifungal activity. This study aimed to investigate the antifungal activity of RM and the underlying mechanisms in Candida albicans (C. albicans). The in vitro antifungal activity of RM was evaluated by a series of experiments, including the XTT reduction assay, confocal laser scanning microscopy assay, scanning electron microscope assay. Results showed that 1 μg/mL RM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Because Candida pathogenicity is associated with changes in morphotype toward pseudohyphae and hyphae, we performed microscopic analyses of in vitro Candida cultures that we stained or did not stain with DAPI to test the effects of lasioglossins LLIII and LLIII-D on temperature-induced morphological differentiation of Candida blastoconidia. In accordance with reports of testing of other antimicrobial peptides for inhibition of Candida morphotype changes (27,28), we observed inhibition of germ tube or hyphae formation by both LLIII and LLIII-D after 24 or 48 hr of incubation. After extended incubation for 72 hr we observed separate hyphae formation in 5% to 15% of total Candida cells.…”
Section: Discussionsupporting
confidence: 92%
“…Because Candida pathogenicity is associated with changes in morphotype toward pseudohyphae and hyphae, we performed microscopic analyses of in vitro Candida cultures that we stained or did not stain with DAPI to test the effects of lasioglossins LLIII and LLIII-D on temperature-induced morphological differentiation of Candida blastoconidia. In accordance with reports of testing of other antimicrobial peptides for inhibition of Candida morphotype changes (27,28), we observed inhibition of germ tube or hyphae formation by both LLIII and LLIII-D after 24 or 48 hr of incubation. After extended incubation for 72 hr we observed separate hyphae formation in 5% to 15% of total Candida cells.…”
Section: Discussionsupporting
confidence: 92%
“…(−)-Stepholidine 20 isolated from rattan stem of Fibraurea recisa had antifungal activity against drug resistant Candida albicans SM372, Candida krusei KM066, Candida parapsilosis SM304160, Cryptococcus neofarms SM9406204 with similar MIC value of 320 µg/mL [91]. Alkaloid (−)-roemerine 49 from the same stem indicated significant inhibition of C. albican transition from yeast to hyphae in a dose dependent manner [92]. Glaucine 68 isolated from the aerial component of Glaucium oxylobum showed moderate skin anti-fungal activities against Microsporum canis, Microsporum gypseum, and Trichophyton mentagrophytes [93].…”
Section: Antimicrobial Activitiesmentioning
confidence: 96%
“…Roemerine (52) at 3.58 lM was also shown to inhibit the formation of a C. albicans biofilm in vitro, possibly related to the cyclic adenosine monophosphate (cAMP) pathway (Ma et al 2015). The toxicity of roemerine was investigated in this study that roemerine had no significant toxicity using Candida elegans worms, three cancer cells and one normal cell (Ma et al 2015). However, roemerine in this study was not observed to have a fungicidal effect against planktonic C. albicans cells.…”
Section: Antifungal Effectsmentioning
confidence: 77%
“…Furthermore, only a single dose of a or b-magnoflorine were used throughout the studies, and thus limited the information on the dose-dependent effect. Roemerine (52) at 3.58 lM was also shown to inhibit the formation of a C. albicans biofilm in vitro, possibly related to the cyclic adenosine monophosphate (cAMP) pathway (Ma et al 2015). The toxicity of roemerine was investigated in this study that roemerine had no significant toxicity using Candida elegans worms, three cancer cells and one normal cell (Ma et al 2015).…”
Section: Antifungal Effectsmentioning
confidence: 93%